A compact dual stopband bandstop filter using defected SIR and Hilbert shape fractal structure. Issue 6 (June 2016) - Sarkar, Pankaj; Pal, Manimala; Ghatak, Rowdra
ABSTRACT: In this paper, a novel technique is proposed to design a dual band bandstop filter which is implemented with two defected stepped impedance resonators (SIRs) embedded on the input output transmission line. The embedded SIRs create a transmission zero at 2.5 GHz that generates the first stopband of the proposed filter. Introducing two Hilbert shaped fractal structure on the ground plane, the second stop band is employed at 3.5 GHz. The overall layout of the filter is realized with a size of 20 × 5 mm 2 . The proposed prototype is EM simulated and measured. The measured −10 dB bandwidth for first stopband is 0.1 GHz and for second stopband it is 0.14 GHz. The measured S‐parameters exhibit an excellent out off band response with insertion loss less than 1.5 dB. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1345–1347, 2016